The Boka Kotorska Bay environment - Joksimović, Aleksandar (Biologist); Djurović, Mirko; Semenov, Aleksandr V. (Professor); Zonn, I. S.; Kostianoy, A. G. (Handbook of environmental chemistry ;, 2017)
This book focuses on environmental aspects of Boka Kotorska Bay in Montenegro (South Adriatic Sea), an area that has been shaped by seasonal tourism, and explores the use and limitations of its natural resources. The individual chapters highlight its geographic and oceanographic characteristics, climate, history and development, biology, fisheries, agriculture, coastal zones, shipping, marine tourism and pollution. Above all, the environmental impact of tourism on marine, coastal and shoreline areas and the resulting conflicts are discussed in detail. The volume is intended for specialists working in various fields of environmental sciences and ecology, water resources and management, land reclamation and agriculture, and regional climate change.